Pengaruh Perubahan Ekonomi terhadap Perkembangan Teori Akuntansi - Atika, Atika; Merah Delima (Budgeting: Jurnal Akuntansi Syariah, 2024)
Abstract This article aims to increase readers' understanding of the influence of economic changes on the development of accounting theory. This article uses a qualitative descriptive method, the type of research is library research, namely through literature review. The data sources in this research are primary data, namely books, articles and also scientific journals. The library study technique is carried out by reading and analyzing written sources related to the research problem in order to obtain discussion results in accordance with the research title. Accounting theory is a concept that represents a systematic description of accounting phenomena by explaining the relationships between variables in an accounting structure, with the aim of being able to predict new phenomena. Accounting theory and practice faces various challenges and criticism along with developments in economics and technology. To overcome this, various parties such as regulators, the accounting profession and business decision makers need to work together to identify and resolve these problems. This is an opportunity to improve and enhance the existing accounting system. Keywords: Theory, Accountinh, Economics, Technology